Testosterone and sexual function in menopausal women based on the Female Sexual Function Index (FSFI) score - Muhammad Agung Khoiri; Muhammad Fidel Ganis Siregar; Sarma Nursani Lumbanraja; Iman Helmi Effendi; Yudha Sudewo; Edy Ardiansyah; Putri Eyanoer (Majalah Obstetri & Ginekologi, 2023)
HIGHLIGHTS Testosterone level correlates with FSFI score, showing that sexual function correlates with hormonal physiology. FSFI is a valid and useful tool in measuring sexual function.   ABSTRACT Objective: This research aimed to analyze the correlation between testosterone levels and sexual function in postmenopausal women. Materials and Methods: This research was a descriptive observational study with a case series approach conducted at Aras Kabu Health Center Outpatient Polyclinic from May to August 2022. The normality test was carried out using the Shapiro-Wilk test. If the data were not normally distributed, data would be analyzed using the Spearman correlation test. If the data were normally distributed, the data analysis would use the Pearson correlation test. Results: There was a significant relationship between Female Sexual Function Index (FSFI) score with testosterone levels and duration of menopause with p<0.05. The degree of correlation found was 0.619 between testosterone levels and FSFI scores, indicating a moderate and significant positive correlation. A correlation degree of 0.482 was found between FSFI and length of menopause which indicated a significant moderate positive correlation, while the degree of correlation between testosterone levels and length of menopause was found to be 0.711, showing a strong and significant positive correlation. Conclusion: There is a significant relationship between FSFI scores with testosterone levels and duration of menopause as well. There was also a significant relationship between testosterone levels and the duration of menopause.